Mesothelioma: cases associated with non-occupational and low dose exposures. Issue 8 (1st August 1999) - Hillerdal, G
Abstract : OBJECTIVES: To estimate the importance of low dose exposure to asbestos on the risk of mesothelioma. METHODS: A review of the literature. RESULTS AND CONCLUSIONS: There is no evidence of a threshold level below which there is no risk of mesothelioma. Low level exposure more often than not contains peak concentrations which can be very high for short periods. There might exist a background level of mesothelioma occurring in the absence of exposure ot asbestos, but there is no proof of this and this "natural level" is probably much lower than the 1-2/million/year which has been often cited.